The pursuit of God : the human thirst for the divine - Tozer, A. W. (Aiden Wilson), 1897-1963. (Camp Hill, Pa. : Christian Publications, 1993)
During a train trip from Chicago to Texas in the late 1940s, A.W. Tozer began to write The Pursuit of God. He wrote all night, the words coming to him as fast as he could put them down. When the train pulled into McAllen, the rough draft was done. Although written in such a remarkably short period of time, the depth, clarity and completeness of Tozer's message has made The Pursuit of God an enduring favorite. - Back cover.
Tozer's legacy -- Following hard after God -- The blessedness of possessing nothing -- Removing the veil -- Apprehending God -- The universal presence -- The speaking voice -- The gaze of the soul -- Restoring the creator-creature relation -- Meekness and rest -- The sacrament of living.
Keywords: God -- Worship and love; Spirituality